Critiquing Computing Artifacts through Programming Satirical Python Scripts - Padiyath, Aadarsh; Nelson-Fromm, Tamara; Ericson, Barbara (2023 Conference on Research in Equitable and Sustained Participation in Engineering, Computing, and Technology (RESPECT), 2023)
Computing artifacts tend to exclude marginalized students, so we must create new methods to critique and change them. We studied the potential for "satirical programming" to critique artifacts as part of culturally responsive computing (CRC) pedagogy. We conducted a one-hour session for three different BPC programs (N=51). We showed an example of a satirical Python script and taught elements of Python to create a script. Our findings suggest this method is a promising CRC pedagogical approach: 50% of marginalized students worked together to create a satirical script, and 80% enjoyed translating their "glitches" into satirical Python scripts.